Model Toleransi Beragama Di Jemaat GMIBM Imanuel Mopuya Wilayah Ibolian Dalam Pandangan Teologi Kristen - Supriyanto, Angga Kurniawan; Najoan, Denny (Educatio Christi, 2022)
This thesis discusses "The Model of Tolerance in the GMIBM Imanuel Mopuya Congregation in the Ibolian Region in the View of Christian Theology." The researcher uses qualitative research methods. Where the researcher focuses research on the GMIBM Imanuel Mopuya Congregation, Ibolian Region with tolerance values that represent a harmonious lifestyle. as social capital, it is able to offer a tolerant relationship pattern that prioritizes the values of mutual respect and mutual help. Religious relations that are preserved are evidence of social relations that foster diversity peacefully and with mutual respect.